Passive cell disruption lipid extraction methods of microalgae for biofuel production – A review. (15th September 2019) - Nagappan, Senthil; Devendran, Saravanan; Tsai, Pei-Chien; Dinakaran, Selvapriya; Dahms, Hans-Uwe; Ponnusamy, Vinoth Kumar
Graphical abstract: Highlights: Passive lipid extraction techniques that skip conventional cell lysis step for microalgal biofuel production. Energy consumption by passive methods are compared with physical methods. In-situ transesterification, saponification-acidification, and switchable solvents have low energy consumption. Passive methods suitable for lipid-based biorefinery is presented. Abstract: The conventional method of lipid extraction mandatorily includes cell lysis which is considered an essential process for the enhancement of extraction efficiency. However, cell lysis method especially those incorporating mechanical and physical methods such as homogenization, sonication, microwave techniques, etc., are energy intensive and drastically escalates the biofuel production cost. Therefore, the development of an alternate route of extraction skipping the conventional mechanical cell lysis step remains a challenge to be accomplished. In this context, we discuss the reports involving passive techniques that are able to extract lipid from microalgae without significant cell wall shearing. This includes methods such as in-situ transesterification, direct saponification, supercritical fluid extraction, organic solvent extraction, etc. Moreover, the review discusses the employment of passive lipid extraction methods in a biorefinery set-up, outlining the various bioproducts that could be generated along with lipid. The review concludes with the analysis of the economics of microalgal lipid extraction using passive disruption methods and compares with the processes incorporating cell lysis steps.